Cognitive Therapy Skills Predict Cognitive Reactivity to Sad Mood Following Cognitive Therapy for Depression - Strunk, Daniel R. (2013)
Both patients’ competence in the coping skills taught in Cognitive Therapy (CT) and patients’ endorsement of dysfunctional cognitions following a sad mood induction (i.e., their cognitive reactivity) have been found to predict risk of relapse following a successful course of CT for depression. We examined the relationship between these constructs, specifically whether CT skills would be related to less cognitive reactivity following a mood induction among patients who responded to a course of CT. In a sample of 28 depressed patients, post-treatment CT skills were significantly related to less cognitive reactivity in response to a sad mood induction procedure (β = −.29). This relation was not accounted for by individual differences in mood reactivity. We discuss these findings as a key step in developing a more complete understanding of the role of CT coping skills and cognitive reactivity as markers of patients’ vulnerability to relapse.